Beyond technology acceptance—a focused ethnography on the implementation, acceptance and use of new nursing technology in a German hospital - Klawunn, Ronny; Albrecht, Urs-Vito; Katzmarzyk, Deliah; Dierks, Marie-Luise (Frontiers in Digital Health, 2024)
Introduction: Hospitalised patients could benefit from the emergence of novel technologies for nursing care. There are numerous technical products available, but these rarely find their way into practice. Further knowledge is required about the circumstances under which technology in nursing is accepted and used. In the research project 'Centre for Implementing Nursing Care Innovations', technical innovations are implemented on a trauma surgery inpatient ward in Germany. After implementation, it was investigated: Which implemented technologies are accepted/rejected, and which factors influence the acceptance/rejection of technology for nurses? Material and methods: A focused ethnography was used, containing two approaches: First, participant observation was conducted to examine nurses' and patients' interaction with technologies. Observations were fixed in a field research diary and analysed using evaluative qualitative content analysis. Second, a questionnaire was used by nurses to provide information about the use frequency and technology suitability. The results of the study were consolidated and analysed using the UTAUT model.Results: Seven studied technologies can be summarised in four result categories: 1) A Mobilising mattress, a Special projector and a Sound pillow are accepted and used by nurses and patients, because they offer a way to provide high quality care with little additional effort. 2) A Fall prevention system is consistently used in patient care as a work obligation, but since nurses consider the system errorprone, acceptance is low. 3) An Interactive therapy ball is accepted but nurses cannot use it due to the high workload. 4) An App for nurse-patient communication and a Work-equipment tracking system are not used or accepted because nurses do not see a practical benefit in the systems.Discussion: Acceptance or rejection of a product does not necessarily equate to use or non-use of the technology. Before implementation, technology acceptance among users occurs as prejudicewhen users are given time to experiment with technology, intention-to-use can stabilize into sustained use. Accepted and used technologies can serve to mask problems (such as staff shortages) and encourage problematic developments, such as the reduction of contact time at the bedside. Therefore, technology acceptance should be qualified in asking to what accepted technology contributes.